Optimum power allocation in V-BLAST with high-level modulation - Yu, Wei (University of Ottawa (Canada), 2009)
Optimal ordering procedure, which is computationally complex in the conventional vertical Bell-labs layered space-time (V-BLAST) algorithm, can be simplified. Among those low-complexity alternatives to the optimal ordering, non-uniform power allocation is intuitively attractive. The unified analysis of power optimized zero forcing (ZF) VBLAST proposed by prior work ([32]) is extended from BPSK to high-level modulations (also known as high-order modulations) by introducing a generic SER approximation---average union bound (AUB)---for multi-path fading channels. This AUB model represents SER by using two parameters related to the constellation---Ds, the normalized minimum Euclidean distance squared and Nc, the average number of the nearest constellation neighbors. First of all, the validity of AUB is demonstrated. Consequently, general average block error rate (BLER) of ZF-VBLAST can be approximated by a closed-form expression of D s and Nc for high-level modulation, the optimum power allocation solution are obtained at high and low SNR. The SNR gain and the robustness of this optimization are also rigorously defined and investigated in a generic manner. Additionally, the above performance variations related to the constellation size are discussed. At last, an efficient Monte Carlo simulation methodology, parallel MatlabRTM, is adopted for the simulations in this thesis. The observations of parallelism efficiency are summarized.
Keywords: Engineering, Electronics and Electrical.